Pengembangan Aplikasi Perangkat Bergerak Sistem Pemesanan Bahan Pangan berbasis Android (Studi Kasus: PT Uni Farm Indonesia) - Farrel Arvino Ilhamsyah; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The problem experienced by PT Uni Farm Indonesia is market expansion and for MSMEs owner is efficiency in their shopping time. This study is aiming to help MSMEs owner in FnB sector to increase the efficiency of their business operations. This study develop android application so user can carry out activities efficiently. This study carried out 4 stages, namely architectural design, database, algorithm and interface. Requirements analysis carried out by forming functional requirement and non functional requirement. System design produces functional and non-functional requirements which are represented in the form of use case diagrams and scenarios. Implementation phase includes database, program code and interface. Testing phase consist of 5 tests, namely blackbox testing, system usability scale (SUS), task scenarios, internationalization testing and compatibility testing. Usability testing produces user satisfaction score of 86.5. The blackbox test produces 100% valid value, and the compatibility and internationalization tests show valid results. The results of the task scenario test show that the user's success rate is 100% and the user's time efficiency is 0.119 tasks/second. The results of the study make it easier for MSME owners to order raw materials efficiently and increase the efficiency of operational activities.